Pengaruh Store Atmosphere, Variasi Minuman dan Transaksi Digital Terhadap Keputusan Pembelian Pada Tomoro Coffee Rantauprapat - Mely Yovani Ritonga Mely; Elida Florentina Sinaga Simanjorang; Mhd Amin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of Store Atmosphere,drink variation, and digital transactions on consumer purchasing decisions at Tomoro Coffee Rantauprapat. The research background is based on the increasing competition among coffee shops in Rantauprapat, which requires business owners to understand the factors influencing consumer behavior. The study employed a quantitative approach, with data collected through questionnaires distributed to 96 respondents who had visited and made purchases at Tomoro Coffee Rantauprapat. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, coefficient of determination, t-test, and F-test. The findings reveal that Store Atmosphere does have positif but not significant on purchasing decisions. In contrast, Minumanvariation and digital transactions have a positive and significant influence on purchasing decisions. Simultaneously, the three independent variables significantly affect purchasing decisions with a contribution of 77.4%, while the remaining 22.6% is influenced by other variables not examined in this study. Therefore, drink variation and digital transactions are proven to be the dominant factors driving consumer purchasing decisions at Tomoro Coffee Rantauprapat.